Technological Changes, Investments, and Unemployment in Indonesia - Ibnu Abbas, Agus Sumanto Muhammad Hasyim; Farida Rahmawati, Santi Merlinda (KnE Social Sciences, 2020)
The vicious circle of poverty in a country could stop if the government was able to solve the problem of unemployment. One way to reduce unemployment is to boost investment. In addition, in the era of the industrial revolution the role of technological development also needs to be considered as a means of reducing unemployment. This study is aiming to analyze the effect of physical investment, educational investment, and technological changes on unemployment in Indonesia. The data used in this study are obtained from Indonesian Central Statistics Agency (BPS). The technological development is proxied by Index of Technology and Communication. The regression method is used to reach the aim of the study. The result of the analysis indicates that the physical investment and technological development have a negative and significant effect on unemployment. Moreover, the findings suggest that the reduction in unemployment in Indonesia is caused by many people who become online motorcycle taxi drivers in the informal sector. Keywords: technology development, physical investment, educational investment, unemployment, panel data